2012
DOI: 10.1016/j.anorl.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Salvage surgery after radiotherapy for oropharyngeal cancer. Treatment complications and oncological results

Abstract: The results of this study confirm the high local complication rate of salvage surgery for oropharyngeal cancer and the poor overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…The median duration of survival was 42.8 months for T1‐T2 and 9.1 months for T3‐T4 ( P = .0039). These results can also be found in the literature, with overall 5‐year survival rates for stages I‐II of 36%‐43.6% versus 11%‐29.1%, respectively …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The median duration of survival was 42.8 months for T1‐T2 and 9.1 months for T3‐T4 ( P = .0039). These results can also be found in the literature, with overall 5‐year survival rates for stages I‐II of 36%‐43.6% versus 11%‐29.1%, respectively …”
Section: Discussionsupporting
confidence: 83%
“…Negative predictive factors seemed to be tumors that were initially at stage IV and when the local recurrences were associated with regional recurrences. In other studies, other factors stood out, such as the lymph node status at the time of the recurrence or the time interval between the end of radiotherapy and the recurrence …”
Section: Introductionmentioning
confidence: 99%
“…Infection was proposed to be one of the risk factors for developing carotid blowout in patients with head and neck cancer . Bacterial infections could also induce vasa vasorum thrombosis and arterial wall injury.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid blowout develops when a damaged arterial wall cannot sustain its integrity against the patient's blood pressure . Previous reports found that incidences of carotid blowout in patients who underwent surgical procedures involving head and neck cancers ranged from 2.9% to 4.3% . In those receiving reirradiation because of recurrent head and neck cancers, the incidences of carotid blowout varied from 2.6% to 10% .…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand is the risk of neck recurrences or microscopic residual disease, on the other hand is the probability of an overtreatment with possible surgical complications (lymphedema, dysphagia, fistulae) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72]. Benefits may include local regional control and OS [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,…”
Section: Introduction: Pros and Consmentioning
confidence: 99%